1995
DOI: 10.1074/jbc.270.36.21009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Phosphorylation in Post-translational Regulation of Protein B23 during Programmed Cell Death in the Prostate Gland

Abstract: Protein B23 is a nucleolar and nuclear matrix-associated phosphoprotein that is involved in ribosome synthesis. Its expression and phosphorylation in rat ventral prostate, an androgen target organ, are profoundly influenced by androgens. Induction of programmed cell death (apoptosis) in the prostatic epithelium by androgen deprivation in the animal induces an early decline in protein B23 in the absence of a corresponding loss of protein B23 mRNA. We have now demonstrated that prostatic nuclei retain the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
6
55
0
Order By: Relevance
“…Some of the apoptosis-inducing chemical agents are known to induce DNA damage as an initial step, which is a distinguishing feature from receptor-mediated apoptosis (21-23). Our previous work employing receptor-mediated apoptosis in the prostate epithelial cells has shown a distinct response of NM-associated CK2 such that a rapid loss of CK2 from the NM compartment temporally precedes the appearance of apoptosis (1,9,11,14,15,24). However, no such studies have been reported on the response of the CK2 signal in relation to chemical-mediated apoptosis in cancer cells.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Some of the apoptosis-inducing chemical agents are known to induce DNA damage as an initial step, which is a distinguishing feature from receptor-mediated apoptosis (21-23). Our previous work employing receptor-mediated apoptosis in the prostate epithelial cells has shown a distinct response of NM-associated CK2 such that a rapid loss of CK2 from the NM compartment temporally precedes the appearance of apoptosis (1,9,11,14,15,24). However, no such studies have been reported on the response of the CK2 signal in relation to chemical-mediated apoptosis in cancer cells.…”
mentioning
confidence: 89%
“…In the same paradigm, androgen withdrawal evoked a rapid loss of nuclear CK2 that was most apparent in the NM fraction. The treatment of castrated rats with androgen, and consequent induction of gene activity and cell growth in the prostatic epithelial cells, concurred with a rapid translocation of the CK2 from cytoplasm to the nuclear compartment such that the enhancement in the NM-associated CK2 was the most prominent (1,2,9,(11)(12)(13).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Phosphorylation of CPTP1-2 and HPTP1B was blocked with the use of known CKII inhibitors, heparin, or poly(Glu.Tyr) (4:1) (Tawfic et al, 1995;Wang et al, 1999) in order to confirm whether the enhancement of phosphatase activity was mainly dependent on the phosphorylation process. The extent of CPTP1-2 phosphorylation was found to be about ten fold lower in the heparin (30 µg/ml) treated CPTP1-2 ( Figure 3A, upper panel, lane 2) in comparison with control.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, nuclear lamins A/C or B have been found to decrease in apoptotic thymocytes [6], T cells [7], and carcinoma cell line [8], [9]. The nucleolar protein B23, an obscure matrix protein has been reported to be degraded early in apoptotic prostate cells [10]. The above mentioned studies were mainly based on the use of immunocytochemical andultra-structural analysis [11], [12].…”
Section: Introductiionmentioning
confidence: 99%